2008
DOI: 10.1016/j.neulet.2008.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory sensory deprivation increases the number of proBDNF-immunoreactive mitral cells in the olfactory bulb of mice

Abstract: In the olfactory bulb, apoptotic cell-death induced by sensory deprivation is restricted to interneurons in the glomerular and granule cell layers, and to a lesser extent in the external plexiform layer, whereas mitral cells do not typically undergo apoptosis. With the goal to understand whether brain-derived neurotrophic factor (BDNF) mediates mitral cell survival, we performed unilateral-naris occlusion on mice at postnatal day one (P1) and examined the subsequent BDNF immunoreactive (BDNF-ir) profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…At the same time, mitral cells appeared to gain BDNF immunoreactivity. We also found that the major BDNF isoform in the OB was the unprocessed BDNF precursor, proBDNF [13]. Neurotrophins are secreted as ‘pro’ isoforms (i.e.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…At the same time, mitral cells appeared to gain BDNF immunoreactivity. We also found that the major BDNF isoform in the OB was the unprocessed BDNF precursor, proBDNF [13]. Neurotrophins are secreted as ‘pro’ isoforms (i.e.…”
Section: Introductionmentioning
confidence: 77%
“…Since the mouse OB expresses more proBDNF than it does mature BDNF [13], we sought to determine if both proBDNF and BDNF were active ligands in the mouse OB. Mitral cells were identified in OB slices as large, pyramidal cells in a discreet layer when viewed with infrared optics [33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…135 Work in mice provides evidence for an odour-elicited activity-based mechanism that enhances synaptogenesis of adult-born periglomerular neurons during their initial phases of development. 136 The reduction in odour-elicited sensory inputs due to deprivation could influence the dynamics and survival of synaptic connection at multiple stages in the olfactory pathway.…”
Section: Odour Deprivation and Odour Perceptionmentioning
confidence: 99%